1999
DOI: 10.1111/j.1467-842x.1999.tb01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain knowledge: a national survey of High School students' knowledge and beliefs about hepatitis C

Abstract: Some lessons from HIV education can be readily transferred to this new epidemic but others cannot. There is a danger that HIV and HCV will be conflated in education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…The lesson from HIV is that education programs must also address the social context of transmission to allow risk-reduction behaviours. 8 Although we found reasonable levels of knowledge of hepatitis C transmission and health significance, we found very low rates of knowledge of the transmission and health consequences of common STIs such as chlamydia and genital herpes. Improving health outcomes in this area will require a concerted effort to improve knowledge of transmission and consequences of these infections.…”
Section: Discussionmentioning
confidence: 63%
“…The lesson from HIV is that education programs must also address the social context of transmission to allow risk-reduction behaviours. 8 Although we found reasonable levels of knowledge of hepatitis C transmission and health significance, we found very low rates of knowledge of the transmission and health consequences of common STIs such as chlamydia and genital herpes. Improving health outcomes in this area will require a concerted effort to improve knowledge of transmission and consequences of these infections.…”
Section: Discussionmentioning
confidence: 63%
“…HIV patients) and young adults had low levels of HCV awareness scoring 54% and 43% correct respectively. This adds to a growing number of investigations showing inadequate HCV knowledge among young adults (20, 21). For example, a recent investigation of an HCV educational campaign for high school students in France showed that baseline knowledge about HCV was poor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature is available in a variety of languages they are all direct translations of the original English format that is aimed at the Anglo‐Celtic, predominantly IDU population. Recent studies have shown that the knowledge of HCV in the general community and in certain high risk groups is variable 28–31 . Race and ethnicity have been shown to influence level of knowledge regarding HCV 32 .…”
Section: Discussionmentioning
confidence: 99%